PERCEPTIONS OF FEMALE STUDENTS IN LEARNING ARABIC IN THE ERA OF GLOBALIZATION AT THE YOGYAKARTA CIVIL TARBIAH SCIENCE COLLEGE - Atikah Safirah; Fadia El Haq; Muqimuddin Husni Arsyad (Proceeding of International Conference of Islamic Education, 2025)
The purpose of this study was to determine how female students of STIT Madani Yogyakarta view Arabic language learning in the era of globalization, as well as the difficulties and solutions they face during the process. The main focus of this study was on their perceptions of the value of Arabic, the challenges they face when studying learning resources such as nahwu and sharaf, and their aspirations for innovative teaching strategies. Data were collected through observation, interviews, and documentation using qualitative methods, and then thematic analysis was conducted. The findings showed that female students viewed Arabic as an important tool for their future academic success and religious understanding. However, they faced limitations in speaking practice, structural grammar problems, and traditional teaching techniques. Female students showed initiative in overcoming these challenges by promoting the use of digital technology in the classroom. They wanted a more relevant, adaptive, and participatory approach to meet the demands of the times. It is hoped that these findings will help educators and institutions create more flexible and successful learning programs.